Factors associated with serious vehicular accidents: A cross‐sectional study in hospital emergency rooms. Issue 2 (12th July 2020) - Forest, Karelle; Valdenaire, Guillaume; Lorendeau, Jean‐Paul; Sagaspe, Patricia; Contrand, Benjamin; Durand‐Teyssier, Charlotte; Sakr, Dunia; Gil‐Jardine, Cédric; Boutreux, Sébastien; Lagarde, Emmanuel; Peyrouzet, Hélène; Lassalle, Régis; et al.
Abstract : Aims: Pictograms on medicine boxes warn of potential drug‐related driving hazard; we studied their association with serious accidents. Methods: Prospective study in emergency departments of the hospitals in Bordeaux and Périgueux (France), of drivers with serious (admitted at least 24 hours) or nonserious vehicular accidents. Minors, passengers, pedestrians or subjects incapable of answering an interview were excluded. Interviews ascertained driver and accident characteristics, use of drugs with or without pictograms, use of alcohol and abuse substances, sleepiness, distractions, and mind wandering at the time of the accident, Results: Between 18 October 2016 and 26 December 2018, 1200 of the 6212 drivers admitted to the hospital emergency rooms, 741 nonserious, 459 serious, were interviewed. Serious accidents were associated with male sex (odds ratio 1.89, 95% confidence interval [1.36–2.64]), age above 60 years (3.64 [2.21–6.00]), driving on local roads (3.34 [2.34–4.76]), driving a motorcycle (3.39 [2.29–5.00]), having drunk alcohol within 6 hours (2.89 [1.85–4.51]) and using a drug with a pictogram during the 24 hours previous to the accident (1.57 [1.06–2.32]). From 207 police reports, 101 drivers were not responsible, and 106 were responsible, associated with age below 40 years, driving in overcast or rainy weather (2.62 [1.29–5.33]), on local roads (3.89 [1.90–7.95]), and use of at least 1 pictogram drug in the previous week (3.12 [1.31–7.41]). Conclusion: The known risks of alcohol and pictogram drugs, of riding motorcycles and using local roads were confirmed. As measured, behavioural sleepiness did not predict accidents.